Matrix-based comparative genomic hybridization: Biochips to screen for genomic imbalances - Solinas Toldo, Sabina; Lampel, Stefan; Stilgenbauer, Stephan; Nickolenko, Jeremy; Benner, Axel; Döhner, Hartmut; Cremer, Thomas; Lichter, Peter (Genes, chromosomes & cancer, 1997)
Comparative genomic hybridization (CGH) to metaphase chromosomes has been widely used for the genome-wide screening of genomic imbalances in tumor cells. Substitution of the chromosome targets by a matrix consisting of an ordered set of defined nucleic acid target sequences would greatly enhance the resolution and simplify the analysis procedure, both of which are prerequisites for a broad application of CGH as a diagnostic tool. However, hybridization of whole genomic human DNA to immobilized single-copy DNA fragments with complexities below the megabase pair level has been hampered by the low probability of specific binding because of the high probe complexity. We developed a protocol that allows CGH to chips consisting of glass slides with immobilized target DNAs arrayed in small spots. High-copy-number amplifications contained in tumor cells were rapidly scored by use of target DNAs as small as a cosmid. Low-copy-number gains and losses were identified reliably by their ratios by use of chromosome-specific DNA libraries or genomic fragments as small as 75 kb cloned in P1 or PAC vectors as targets, thus greatly improving the resolution achievable by chromosomal CGH. The ratios obtained for the same chromosomal imbalance by matrix CGH and by chromosomal CGH corresponded very well. The new matrix CGH protocol provides a basis for the development of automated diagnostic procedures with biochips designed to meet clinical needs. Genes Chromosomes Cancer 20:399-407, 1997. © 1997 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 7. Dezember 1998
Gesehen am 31.10.2024